Novel of (PLA/PCL blend)/Gd2O3 rare earth oxide nanocomposites: Shape memory effect, thermal, magnetic, and mechanical properties - Oner, Ecem Ozen; Pekdemir, Mustafa Ersin; Ercan, Ercan; Say, Yakup; Kok, Mediha; Aydogdu, Yildirim (Wiley, 2022)
Poly e-caprolactone (PCL) and poly lactic acid (PLA) stand out as biocompatible polymers. In this study, PCL and PLA were blended in 40:60 ratio, respectively, and then the Gd2O3 compound, which is an important earth element oxide, was mixed in PLA-PCL shape memory polymer (SMP) blend at different rates and polymer blend nanocomposites were obtained. First of all, the effects of Gd2O3 oxide on the thermal properties of the SMP blend were determined with a differential scanning calorimeter (DSC) and thermogravimetric analyzer (TGA), and it was determined that Gd2O3 did not have a significant effect on the melting temperature of the blend, while it significantly increased its thermal stability. As a result of the XRD (X-ray diffraction) analysis of the composites at room temperature, it was determined that the semicrystalline blend, with the addition of Gd2O3, increased its crystalline property. When the shape memory effect was examined, it was understood that the additive did not eliminate the shape memory effect. When the magnetic property of the gadolinium oxide-doped composite, which is magnetocaloric oxide, was examined, the magnetic property of the composite changed from diamagnetic to paramagnetic with increasing additives. Finally, the mechanical properties of the shape memory blend composite were investigated and no regular changes were observed in the mechanical properties with increasing Gd2O3.
Keywords: blend; Gd2O3; magnetic behavior; mechanical property; poly e-caprolactone; poly lactic acid; rare earth oxide